Cover Feature: Probing DNA Dynamics: Stacking‐Induced Fluorescence Increase (SIFI) versus FRET (ChemPhotoChem 9/2020). Issue 9 (27th August 2020) - Morten, Michael J.; Steinmark, I. Emilie; Magennis, Steven W.
Abstract : The Cover Feature depicts the fluorescent dye Cy3 stacking in a gap in a DNA double helix. The Cy3 emission can be strongly enhanced upon stacking, which is used here to report on DNA structure and dynamics. More information can be found in the Communication by Dr. Steven W. Magennis and co‐workers . The Tetris trade dress is owned by Tetris Holding, used with permission .